Using True Colors® to Match Individual’s Personality Traits with the Appropriate Volunteer Role for Success - Alayne Torretta; Laura Bovitz ([TEST] Journal of Extension, 2021)
Just as there are different reasons that people volunteer in the community, each volunteer has specific values, different needs to be fulfilled, and different strengths to offer to Extension programs. Understanding these characteristics and utilizing them in assigning the appropriate volunteer role will result in more success in their volunteer experience. Utilizing True Colors® when assigning volunteer roles and developing working groups and committees has proven effective in our county 4-H programs. Conflicts between volunteers who do not work well together have been lessened due to reassigning them to roles that best fit their personality types.
Keywords: volunteers; conflict resolution personality; Communication